A monstrous reading of selected mothers in Malay folktales - Ramlan, Wan Nur Madiha; Fateha, Nurul (2020)
Mothers often play a principal role in many oral traditions and popular cultures around the globe as they often embody the archetypal maternal and feminine. Time and again, the figure of the Mother occupies a complex, often ambiguous space within cultural imaginaries, in which she is both glorified (“good”) and vilified (“bad”). This paper adapts Jeffrey Cohen’s monster culture as a framework to perform a monstrous reading of selected vilified mothers in Malay folktales. The word “monster” comes from Latin “monstrum,” meaning to reveal and to warn. In relation to the word’s etymology, we thus explore the demonisation of the stepmother in “Bawang Putih Bawang Merah,” both of the vengeful mothers in the tales of “Si Tenggang” and “Batu Belah Batu Bertangkup,” and last but not least, the controversial, Scarlet Letter-esque mother in “Lancang Kuning.” Here, we consider the possible revelations or warnings that might have resulted from the particular monstrosity of these mothers, relating these findings to Bascom’s four functions of folklore. At the end of this paper, we will demonstrate that these tales can be read as an expression of female anxiety in a patriarchal society and a temporary exit from the ideals of motherhood.